The drying of red oak at vacuum pressure - Pérez Ricardez, Agustín; Rivera Suárez, Juan; Aviña Berumen, Luis (Maderas. Ciencia y Tecnología, 2014)
In memoriam of Dr. H. Peter STEINHAGEN In this work we present a mathematical model to predict the red oak wood vacuum drying kinetics. The mathematical model considers molecular diffusion and two-dimensional flow of humidity. The experimental work was carried out in controlled conditions of temperature and relative humidity to estimate the effective diffusion coefficient and moisture content in the wood. An “Arrhenius” type expression was employed for temperature dependence of diffusion coefficient.